Marvel-verse: she-hulk ebook - Lee, Stan (Marvel Worldwide, Inc., 2021)
Collects Savage She-Hulk (1980) #1, Sensational She-Hulk (1989) #4, Avenging Spider-Man (2011) #7, Guardians Team-Up (2015) #4, material from King-Size Spider-Man Summer Special (2008) #1. She may have started out Savage, but there's no doubt She-Hulk is the Marvel-Verse's most Sensational hero — and these are the adventures that prove it! Discover how a lifesaving blood transfusion from her cousin, Bruce Banner, led to a green-skinned transformation for lawyer Jennifer Walters! As the emerald attorney interviews for a new law firm, Jen meets the legendary Blonde Phantom! While She-Hulk takes on the Mutant Registration Act in court, her archfoe Titania, causes serious disorder! But Jen's most important case of all comes when she's accused of crimes against the space-time continuum — and if she's found guilty, the sentence is complete erasure from reality! Plus: A night at the museum…with Spider-Man!